Analysis and Evaluation of Contamination Status of Polycyclic Aromatic Hydrocarbons (PAHs) in Settled House and Road Dust Samples from Hanoi - Anh, Hoang Quoc; Takahashi, Shin; Thao, Duong Thi; Thai, Nguyen Hung; Khiet, Pham Thanh; Hoa, Nguyen Thi Quynh; Quynh, Le Thi Phuong; Da, Le Nhu; Minh, Tu Binh; Tri, Tran Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4DO - 10.25073/2588-1140/vnunst.4943, 2019)
Concentrations of 16 polycyclic aromatic hydrocarbons (PAHs) were determined in settled house dust and road dust samples collected from a core urban area of Hanoi. Levels of PAHs ranged from 830 to 3500 (median 2000) ng/g in house dust, and from 1400 to 4700 (median 1700) ng/g in road dust. Concentrations of PAHs in dust samples of this study were within the moderate range as compared with those from other countries in the world. Toxic equivalents to benzo[a]pyrene (BaP-EQs) in our samples ranged from 81 to 850 (median 330) ng BaP-EQ/g with principal contributors as BaP and dibenz[a,h]anthracene, which accounted for 69% to 93% of BaP-EQs. In almost all the samples, proportions of high-molecular-weight PAHs (HMW-PAHs with 4–6 rings) were higher than those of low-molecular-weight PAHs (LMW-PAHs with 2–3 rings), suggesting emission sources from combustion processes rather than direct contamination by petrogenic sources. Traffic activities were estimated as important sources of PAHs in the studied areas, for example, vehicular exhaust and tire debris. Keywords: PAHs, house dust, road dust, traffic emission, urbanization. References [1] K. Srogi, Monitoring of environmental exposure to polycyclic aromatic hydrocarbons: a review, Environ. Chem. Let. 5 (2007) 169-195. https://doi. org/10.1007/s10311-007-0095-0. [2] K.H. Kim, S.A. Jahan, E. Kabir, R.J.C. Brown, A review of airborne polycyclic aromatic hydrocarbons (PAHs) and their human health effects. Environ. Int. 60 (2013) 71–80. https://doi. org/10.1016/j.envint.2013.07.019. [3] E. Stogiannidis, R. Laane, Source characterization of polycyclic aromatic hydrocarbons by using their molecular indices: an overview of possibilities. Rev. Environ. Contam. Toxicol. 234 (2015) 49–133. https://doi.org/10.1007/978-3-319-10638-0_2. [4] H.I. Abdel-Shafy, M.S.M. Mansour, A review on polycyclic aromatic hydrocarbons: source, environmental impacts, effect on human health and remediation. Egypt. J. Pet. 25 (2016) 107–123. https://doi.org/10.1016/j.ejpe.2015.03.011. [5] ATSDR, 1995. Toxicological profile for polycyclic aromatic hydrocarbons. https://www.atsdr.cdc. gov/toxprofiles/tp69.pdf. [6] M.T. Anh, L.M. Triet, J.J. Sauvain, J. Tarradellas, PAH contamination levels in air particles and sediments of Ho Chi Minh City, Vietnam. Bull. Environ. Contam. Toxicol. 63 (1999) 728–735. https://doi.org/10.1007/s00128 9901040. [7] T.T. Hien, L.T. Thanh, T. Kameda, N. Takenaka, H. Bandow, Distribution characteristics of polycyclic aromatic hydrocarbons with particle size in urban aerosols at the roadside in Ho Chi Minh City, Vietnam. Atmos. Environ. 41 (2007) 1575–1586. https://doi.org/10.1016/j.atmosenv. 2006.10.045. [8] M. Kishida, K. Imamura, N. Takenaka, Y. Maeda, P.H. Viet, H. Bandow, Concentrations of atmospheric polycyclic aromatic hydrocarbons in particulate matter and the gaseous phase at roadside sites in Hanoi, Vietnam. Bull. Environ. Contam. Toxicol. 81 (2008) 174–179. https://doi. org/10.1007/s00128-008-9450-5. [9] H.Q. Anh, K. Tomioka, N.M. Tue, L.H. Tuyen, N.K. Chi, T.B. Minh, P.H. Viet, S. Takahashi, A preliminary investigation of 942 organic micro-pollutants in the atmosphere in waste processing and urban areas, northern Vietnam: levels, potential sources, and risk assessment. Ecotoxicol. Environ. Saf. 167 (2019) 354–364. https://doi.org/10.1016/j.ecoenv.2018.10.026. [10] C.V. Hung, B.D. Cam, P.T.N Mai, B.Q. Dzung, Heavy metals and polycyclic aromatic hydrocarbons in municipal sewage sludge from a river in highly urbanized metropolitan area in Hanoi, Vietnam: levels, accumulation pattern and assessment of land application. Environ. Geochem. Health 37 (2015) 133–146. https:// doi.org/10.1007/s10653-014-9635-2. [11] C.T. Pham, N. Tang, A. Toriba, K. Hayakawa, Polycyclic aromatic hydrocarbons and nitropolycyclic aromatic hydrocarbons in atmospheric particles and soil at a traffic site in Hanoi, Vietnam. Polycycl. Aromat. Comp. 35 (2015) 355–371. https://doi.org/10.1080/10406 638.2014.903284. [12] H.Q. Anh, K. Tomioka, N.M. Tue, G. Suzuki, T.B. Minh, P.H. Viet, S. Takahashi, Comprehensive analysis of 942 organic micro-pollutants in settled dusts from northern Vietnam: pollution status and implications for human exposure. J. Mater. Cycles Waste Manag. 21 (2019) 57–66. https://doi.org/10.1007/s101 63-018-0745-2. [13] L.H. Tuyen, N.M. Tue, G. Suzuki, K. Misaki, P.H. Viet, S. Takahashi, S. Tanabe, Aryl hydrocarbon receptor mediated activities in road dust from a metropolitan area, Hanoi-Vietnam: contribution of polycyclic aromatic hydrocarbons (PAHs) and human risk assessment. Sci. Total Environ. 491-492 (2014) 246–254. https://doi.org/10.1016/j.scitotenv.2014. 01.086. [14] L.H. Tuyen, N.M. Tue, S. Takahashi, G. Suzuki, P.H. Viet, A. Subramanian, K.A. Bulbule, P. Parthasarathy, A. Ramanathan, S. Tanabe, Methylated and unsubstituted polycyclic aromatic hydrocarbons in street dust from Vietnam and India: occurrence, distribution and in vitro toxicity evaluation. Environ. Pollut. 194 (2014) 272–280. https://doi.org/10.1016/j.envpol. 2014.07.029. [15] H.Q. Anh, T.M. Tran, N.T.T. Thuy, T.B. Minh, S. Takahashi, Screening analysis of organic micro-pollutants in road dusts from some areas in northern Vietnam: a preliminary investigation on contamination status, potential sources, human exposures, and ecological risk. Chemosphere 224 (2019) 428–436. https://doi.org/10.1016/j. chemosphere.2019.02.177. [16] H.T.T. Thuy, T.T.C. Loan, T.H. Phuong, The potential accumulation of polycyclic aromatic hydrocarbons in phytoplankton and bivalves in Can Gio coastal wetland, Vietnam. Environ. Sci. Pollut. Res. 25 (2018) 17240–17249. https://doi. org/10.1007/s11356-018-2249-y. [17] P.C. Van Metre, B.J. Mahler, J.T. Wilson, PAHs underfoot: contaminated dust from coal-tar sealcoated pavement is widespread in the United States. Environ. Sci. Technol. 43 (2009) 20–25. https://doi.org/10.1021/es802119h. [18] L. Liu, A. Liu, Y. Li, L. Zhang, G. Zhang, Y. Guan, Polycyclic aromatic hydrocarbons associated with road deposited solid and their ecological risk: Implications for road stormwater reuse. Sci. Total Environ. 563–564 (2016) 190–198. https://doi.org/10.1016/j.scitotenv.2016.04.114. [19] X. Zheng, Y. Yang, M. Liu, Y. Yu, J.L. Zhou, D. Li, PAH determination based on a rapid and novel gas purge-microsyringe extraction (GP-MSE) technique in road dust of Shanghai, China: Characterization, source apportionment, and health risk assessment. Sci. Total Environ. 557–558 (2016) 688–696. https://doi.org/10.1016/j. scitotenv.2016.03.124. [20] T.T. Dong, B.K. Lee, Characteristics, toxicity, and source apportionment of polycyclic aromatic hydrocarbons (PAHs) in road dust of Ulsan, Korea. Chemosphere 74 (2009) 1245–1253. https: //doi.org/10.1016/j.chemosphere.2008.11.035. [21] R. Khanal, H. Furumai, F. Nakajima, C. Yoshimura, Carcinogenic profile, toxicity and source apportionment of polycyclic aromatic hydrocarbons accumulated from urban road dust in Tokyo, Japan. Ecotoxicol. Environ. Saf. 165 (2018) 440–449. https://doi.org/10.1016/j. ecoenv.2018.08.095. [22] N. Soltani, B. Keshavarzi, F. Moore, T. Tavakol, A.R. Lahijanzadeh, N. Jaafarzadeh, M. Kermani, Ecological and human health hazards of heavy metals and polycyclic aromatic hydrocarbons (PAHs) in road dust of Isfahan metropolis, Iran. Sci. Total Environ. 505 (2015) 712–723. https://doi.org/10.1016/j.scitotenv.2014.09.097. [23] B.A.M. Bandowe, M.A. Nkansah, Occurrence, distribution and health risk from polycyclic aromatic compounds (PAHs, oxygenated-PAHs and azaarenes) in street dust from a major West African Metropolis. Sci. Total Environ. 553 (2016) 439-449. https://doi.org/10.1016/j. scitotenv.2016.02.142. [24] T.C. Nguyen, P. Loganathan, T.V. Nguyen, S. Vigneswaran, J. Kandasamy, D. Slee, G. Stevenson, R. Naidu, Polycyclic aromatic hydrocarbons in road-deposited sediments, water sediments, and soils in Sydney, Australia: Comparisons of concentration distribution, sources and potential toxicity. Ecotoxicol. Environ. Saf. 104 (2014) 339–348. https://doi.org/10.1016/j.ecoenv.2014.03.010. [25] C. Y. Kuo, H.C. Chen, F.C. Cheng, L.R. Huang, P.S. Chien, J.Y. Wang, Polycyclic aromatic hydrocarbons in household dust near diesel transport routes. Environ. Geochem. Health 34 (2012) 77–87. https://doi.org/10.1007/s10653-011-9392-4. [26] W. Wang, F.Y. Wu, J.S. Zheng, M.H. Wong, Risk assessments of PAHs and Hg exposure via settled house dust and street dust, linking with their correlations in human hair. J. Hazard. Mater. 263 (2013) 627–637. https://doi.org/10.1016/j.jhazmat. 2013.10.023. [27] N. Ali, I.M.I. Ismail, M. Khoder, M. Shamy, M. Alghamdi, M. Costa, L.N. Ali, W. Wang, S.A.M.A.S. Eqani, Polycyclic aromatic hydrocarbons (PAHs) in indoor dust samples from cities of Jeddah and Kuwait: levels, sources and non-dietary human exposure. Sci. Total Environ. 573 (2016) 1607–1614. https://doi.org/10.1016/j. scitotenv.2016.09.134. [28] M.Y. Civan, U.M. Kara, Risk assessment of PBDEs and PAHs in house dust in Kocaeli, Turkey: levels and sources. Environ. Sci. Pollut. Res. 23 (2016) 23369–23384. https://doi.org/10. 1007/s11356-016-7512-5. [29] A. Maragkidou, S. Arar, A. Al-Hunaiti, Y. Ma, S. Harrad, O. Jaghbeir, D. Faouri, K. Hämeri, T. Hussein, Occupational health risk assessment and exposure to floor dust PAHs inside an educational building. Sci. Total Environ. 579 (2017) 1050–1056. https://doi.org/10.1016/j.scitotenv.2016. 11.055. [30] I.C. Yadav, N.L. Devi, J. Li, G. Zhang, Polycyclic aromatic hydrocarbons in house dust and surface soil in major urban regions of Nepal: implication on source apportionment and toxicological effect. Sci. Total Environ. 616–617 (2018) 223–235. https://doi.org/10.1016/j.scitotenv.2017.10.313. [31] R. Boonyatumanond, M. Murakami, G. Wattayakorn, A. Togo, H. Takada, Sources of polycyclic aromatic hydrocarbons (PAHs) in street dust in a tropical Asian mega-city, Bangkok, Thailand. Sci. Total Environ. 384 (2007) 420−432. https://doi.org/10.1016/j.scitotenv. 2007.06.046. [32] I. Sadiktsis, C. Bergvall, C. Johansson, R. Westerholm, Automobile tire–a potential source of highly carcinogenic dibenzopyrenes to the environment. Environ. Sci. Technol. 46 (2012) 3326−3334. https://doi.org/10.1021/es204257d. [33] M. Howsam, K.C. Jones, Sources of PAHs in the environment. In: Neilson, A.H. (Ed.), The Handbook of Environmental Chemistry Vol. 3 Part I PAHs and Related Compounds. Springer-Verlag, Berlin, Heidelberg (1998) 137–174. https://doi.org/10.1007/978-3-540-49697-7_4. [34] I.C.T. Nisbet, P.K. Lagoy, Toxic equivalency factors (TEFs) for polycyclic aromatic hydrocarbons (PAHs). Regul. Toxicol. Pharmacol. 16 (1992) 290–300. https://doi.org/10. 1016/0273-2300(92)90009-X. [35] B. Pieterse, E. Felzel, R. Winter, B. van der Burg, A. Brouwer, PAH-CALUX, an optimized bioassay for AhR-mediated hazard identification of polycyclic aromatic hydrocarbons (PAHs) as individual compounds and in complex mixtures. Environ. Sci. Technol 47 (2013) 11651–11659. https://doi.org/10.1021/es403810w. [36] M.B. Yunker, R.W. Macdonald, R. Vingarzan, R. H. Mitchell, D. Goyette, S. Sylvestre, PAHs in the Fraser River basin: a critical appraisal of PAH ratios as indicators of PAH source and composition. Org. Geochem. 33 (2002) 489–515. https://doi.org/10.1016/S0146-6380(02)00002-5. [37] M. Saha, A. Togo, K. Mizukawa, M. Murakami, H. Takada, M.P. Zakaria, N.H. Chiem, B.C. Tuyen, M. Prudente, R. Boonyatumanond, S.K. Sarkar, B. Bhattacharya, P. Mishra, T.S. Tana, Sources of sedimentary PAHs in tropical Asian waters: differentiation between pyrogenic and petrogenic sources by alkyl homolog abundance. Mar. Pollut. Bull. 58 (2009) 189–200. https://doi.org/10.1016/j.marpolbul.2008.04.049.